Utilizing Information Technology to Spread Religious Values in a Moderate Manner - Ramadhan Laleno, Hamim Mumtaz; Arsalan, Fikri Ahmad; Wijaya, Radite Akbar; Fadhil, Abdul (Jurnal Multidisiplin Indonesia, 2025)
In today's digital era, developments in information and communication technology have opened up new opportunities for the broader and more interactive dissemination of religious values. This study aims to examine the role of digital media as a means of moderate da'wah, highlighting the transformation of da'wah methods from traditional to online platforms, the opportunities for two-way interaction, and the challenges of negative content such as misinformation and radicalism. The method used is qualitative research with a library research approach, where data was obtained from scientific journals, books, online articles, and recent research reports. Content analysis was conducted to examine theories, concepts, and previous studies related to moderate digital da'wah. The results show that social media, such as Facebook, YouTube, Twitter, Instagram, and Telegram, are effective vehicles for spreading Islamic teachings ?, as long as the content is packaged creatively and responsibly. The concept of religious moderation plays a crucial role in maintaining message balance, preventing polarization, and maintaining harmony in the digital space. Furthermore, the active participation of the younger generation through short video content, Islamic podcasts, and educational threads strengthens the narrative of moderate da'wah. This study recommends improving religious digital literacy and collaboration between religious scholars, IT practitioners, and youth communities to optimize inclusive da'wah in the digital era.